Service quality and institutional reputation on student’s loyalty - Muhammad Bakrie; Tri Widayatsih; Ning Herlina (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This study highlights the effect of service quality and the reputation of private higher institutions in building student loyalty. This research uses a quantitative approach with a survey method. The research respondents were 185 students from PGRI Palembang University. Analysis techniques using variance-based structural equation models (SEM) SmartPLS. The results of the study indicate that the quality of service has a significant direct effect on reputation, not a significant direct effect on student loyalty. Institutional reputation has a very significant direct effect on loyalty. Student service quality has a significant indirect effect on student loyalty through the reputation of the institution, this implies that the reputation of the institution carries an influence relationship (antecedents) between service quality variables on student loyalty. These findings can help higher education institutions to make better strategic plans to increase student loyalty through improving the quality of service and the reputation of the institution.